Pelatihan mengolah tanah, pupuk organik, pestisida herbal dan pengolahan pasca panen petani sayuran Desa Cikidang Kecamatan Lembang - Sri Handayani; Kamin Sumardi; Dewi Cakrawati (Universitas Pendidikan Indonesia, 2014)
Cikidang Village Lembang that is included to sub-district of Lembang, and West Bandung district has a land area of 523 861 ha where 80% of the total area is agricultural land of productive vegetable. Efforts to help increase the level of skills in agriculture, especially vegetable farmers have been made by several parties. But the quality, quantity and level continuity are not run well yet. There are still many farmers and farm workers who do not understand how good farming. For example, how to process the land exactly, good fertilization, making their own fertilizer, making pesticides with organic material and post-harvest handling of vegetables so that the product has added value for the farmer. One of effort that is done in help farmers improving the quality of the vegetables is to give more technical training, practical and sustainable agriculture on environmentally friendly by using fertilizers and pesticides derived from nature. Training itself needs to be done gradually through the approach of persuasion, collaborative and participatory. Persuasion approach is done in order that the farmers do not feel to be taught, dictated or forced in terms of farming knowledge. Collaborative approach is taken to encourage farmer directly to practice without too much theory by involving farmer groups and local community leaders' farmer. Moreover, the Collaborative approach is recognized very important, because they feel that they are invited to cooperate and appreciated. The participatory approach is used to bring farmers together to do good farming activities. This approach is done so that the farmers can feel all phases of good farming directly and also they are actively involved.